A family study of Paget's disease of bone. Issue 3 (September 1983) - Sofaer, J A; Holloway, S M; Emery, A E
Abstract : Familial aggregation of Paget's disease of bone occurs occasionally and an exclusively genetic aetiology has been proposed in the past. On the other hand, epidemiological surveys point to an important environmental contribution, and evidence is accumulating to suggest that the disease may be caused by a slow virus infection. Analysis of 407 family history questionnaires completed by patients with Paget's disease confirmed the familial nature of the disease. Overall, the findings were consistent with the hypothesis that Paget's disease is caused by infection with a common and widespread virus superimposed on genetic variation for susceptibility and perhaps severity of the disease.